Bibliometric Analysis of Supply Chain Management: An International Journal from 2005-2014 - Anil Kumar; Dr. G.S. Kushwaha (International Journal of Supply Chain Management, 2015)
The purpose of this paper is to analyse the contributions of researchers in the field of management internationally through this journal in last ten years. Authors conduct a bibliometric analysis of the Supply Chain Management: an International Journal which is indexed in the Social Science Citation Index. This study was developed from a bibliometric survey to expand knowledge regarding publications in the supply chain management: an international journal from 2005-14. The present study Bibliometric analysis of Supply chain management: an international journal which covers the 458 articles of 10 volumes and 59 issues in 10 years from 2005-2014. Authors performed the analysis of scientific publications, reviewed and indexed in databases Emerald. Nonparametric test X2 was done to test the hypotheses. The Authors attempted to reveal the year wise publication of articles, authorship pattern of articles, citation pattern, No of citations, country wise distribution of articles, average number of citation per articles and length of papers etc. Results showed that, in the year 2006, highest 59(12.94%) articles were published out of 458 articles in last ten years. Dual author contribution has predominant with 35.80%. In geographical distribution of articles, UK has contributed highest 103 articles with 22.49% and highest 49.56% articles are published with page range of 11-20. The X2 test depict that there is significant relationship between highly cited articles and the most productive author while there is no significant relationship between highly cited articles and the most productive country as well as most productive institute/university. The limitation of this study is that articles were taken from 2005-14 only and the citations are taken from the Google scholar only. First, this research could be used for further analysis in the future such as keyword content analysis of getting the deeper knowledge. Second, only one SSCI Journal was considered in this research. Therefore, future research could use the different journal databases to retrieve more in-depth issues. This study will helpful for researchers to know which article and which author has major contribution and what kind of study he has done in the past 10 years as well as what will be the future scope. The study is first of its kind with reference to this journal and thus it will contribute to the researchers to enhance the knowledge /information about the kind of study being published in this journal in last ten years.